Efficacy and safety of ultralow doses of drospirenone and 17β-estradiol in postmenopausal women meta-analysis - O. R. Grigoryan (Медицинский совет, 2018)
Vasomotor symptoms, including hot flashes (HF), are the most common symptoms of the menopause, which require the hormone replacement therapy with estrogens and/or progestogens. Recent international clinical guidelines recognize the need to use the lowest effective doses of hormone therapy. Drospirenone (DRSP) in combination with 17β-Estradiol (E) is used as hormone therapy (HT) to relieve the postmenopausal symptoms and prevent osteoporosis. The objective of this review is to perform a meta-analysis of the studies evaluating the efficacy and safety of low-dose E2 and DRSP for the treatment of vasomotor symptoms of menopausal syndrome, as well as assessing the state of the endometrium in postmenopausal women. The review presents data from the largest randomized controlled trials that evaluated the lowest effective dose of the E2/DRSP combination, the safety of this dose for endometrium, idetified features of its pharmacokinetics and pharmacodynamics, depending on various factors. The first randomized trial showed that 0.25 mg/E2 DRSP 0.5 mg combination is the lowest effective dose for the relief of HF in postmenopausal women. The efficacy of low doses of DRSP/E2 correlated with E2 and DRSP exposure in serum, while smoking adversely affected the effectiveness of treatment. Evaluation of the risk of endometrial hyperplasia and bleeding peculiarities on the background of DRSP reception 0.25 mg/E2 0.5 mg for 12 months did not reveal hyperplasia or atypia of the endometrium, which confirmed the safety profile of the DRSP 0.25 mg/E2 0.5 mg combination. Thus, 0.25 mg/E2 0.5 mg DRPP is the lowest effective dose for relieving HF, which does not significantly affect the endometrial state. DRSP 0.25 mg/E2 0.5 mg reverses vasomotor manifestations of menopausal syndrome, reduces the frequency and severity of genitourinary syndrome symptoms, which, in turn, improves the patients’ quality of life.